Dampak Liquidity pada Hubungan antara Sustainability Reporting dan Kinerja Keuangan (Studi pada Perusahaan Manufaktur BEI) - Retnosari, Retnosari; Nurcahya, Yulida Army; Astutik, Erni Puji (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Purpose of this study is to test and empirically prove the effect of sustainability reporting and liquidity on financial performance, as well as the impact of liquidity on the relationship between sustainability reporting and financial performance. The population of this study were all manufacturing companies listed on the Indonesian stock exchange in 2016-2018 with purposive sampling as the basis for research sampling. The hypothesis in this study was tested using Moderating Regression Analysis. The results showed that the sustainability reporting variable had an influence on financial performance, and the liquidity variable had no effect on financial performance and did not moderate the effect of the sustainability reporting variable on financial performance